Preservation of Bilateral Corticospinal Projections from Injured Hemisphere After Perinatal Stroke - Cameron P. Casey; Ellen N. Sutter; Alina Grimaldo; Kellie M. Collins; Jose Guerrero-Gonzalez; Ryan M. McAdams; Douglas C. Dean; Bernadette T. Gillick (Brain Sciences)
Background: Perinatal brain injury is a leading cause of developmental disabilities, including cerebral palsy. However, further work is needed to understand early brain development in the presence of brain injury. In this case report, we examine the longitudinal neuromotor development of a term infant following a significant loss of right-hemispheric brain tissue due to a unilateral ischemic stroke. Our analysis focuses on the integrity and development of the corticospinal tract (CST) from the lesioned hemisphere. This case provides a unique opportunity to evaluate CST development after loss of the majority of the motor cortex. Methods: Evaluations were conducted when the infant was 4 (Visit-1), 18 (Visit 2), and 25 (Visit 3) months old. Assessments included magnetic resonance imaging (MRI) to characterize the lesion and quantify CST structural integrity, single-pulse transcranial magnetic stimulation (spTMS) to evaluate CST functional circuitry, and neuromotor assessments. Results: At Visit 1, bilateral CSTs were identified through diffusion-weighted MRI (dMRI) despite an estimated loss of 92.7% (7.3% retained) of age-typical motor cortex from the right hemisphere. Both hemispheres exhibited bilateral motor-evoked potential in response to stimulation with spTMS, which remained when reassessed at Visits 2 and 3. Longitudinal MRI showed distinct developmental trajectories of CST integrity in each hemisphere, with the lesioned hemisphere exhibiting initial increases in integrity between Visits 1 and 2 followed by a decrease in integrity between Visits 2 and 3. The non-lesioned hemisphere showed increased integrity from Visit 1 to Visit 2, which remained stable at Visit 3. Motor assessments at all visits indicated a high risk of cerebral palsy. Conclusions: This report highlights the utility of MRI and spTMS in studying neuromotor development. The findings reveal preserved functional bilateral CST circuitry despite majority loss of the right-hemispheric motor cortex as well as distinct developmental trajectories in CST integrity between hemispheres. These results underscore the potential for neural plasticity after perinatal brain injury. Clinical Trials Registration: NCT05013736.